PENGARUH PEMUASAAN TERHADAP UMUR PERMULAAN BERTELUR DAN BOBOT TELUR PERTAMA PADA BURUNG PUYUH (Coturnix coturnix japonica) - Nani Zurahmah (Politeknik Pembangunan Pertanian Bogor, 2020)
This experiment was conducted to investigate the effect of fasting at grower period (3 to 6 weeks of age) on the onset of laying (sexual maturity age) and the first egg weight of Japanese quail (Coturnix coturnix japonica). Three hundred and forty female of Japanese quails at 3 week of age were used in this experiment. The treatments were P0 (without fasting or control), P1 (skip-a-day fasting), P2 (nighttime fasting: 18.00 p.m to 06.00 a.m.), and P3 (daytime fasting: 06.00 a.m to 18.00 p.m.). The fasting treatments affected significantly (P<0.01) on delaying the onset of laying (sexual maturity) (P0 = 40.6 days; P1 = 49.2 days; P2 = 45.3 days; P3 = 45.2 days), but did not affect the first egg weight (P0 = 8.8 g; P1 = 9.7 g; P2 = 8.8 g; P3 = 9.7 g).